2014
DOI: 10.1021/jp503816r
|View full text |Cite
|
Sign up to set email alerts
|

Structure and Properties of DNA in Apolar Solvents

Abstract: The study of nucleic acids in low-polarity environments paves the way for novel biotechnological applications of DNA. Here, we use a repertoire of atomistic molecular simulation tools to study the nature of DNA when placed in a highly apolar environment and when transferred from aqueous to apolar solvent. Our results show that DNA becomes stiffer in apolar solvents and suggest that highly negatively charged states, which are the most prevalent in water, are strongly disfavored in apolar solvents and neutral st… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
26
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 27 publications
(26 citation statements)
references
References 56 publications
0
26
0
Order By: Relevance
“…Mixtures of organic solvents and water could be better solvating agents than either of the individual solvents because the water and organic molecules can orient to minimize conformational stress around a nucleotide chain (Hammouda and Worcester 2006). A study using molecular dynamics simulations showed that a small number of highly stable water molecules and neutralization of phosphate charges are crucial requirements for the transfer of a 7-base-pair DNA duplex from water to an apolar medium such as carbon tetrachloride (Arcella et al 2014). Solvation of nucleotides in organic solutions in the presence of a small amount of water is a complex phenomenon that depends on the nature of the environment to which the nucleic acids are initially exposed (Ababneh et al 2003).…”
Section: Organic Solutions With a Small Amount Of Watermentioning
confidence: 99%
“…Mixtures of organic solvents and water could be better solvating agents than either of the individual solvents because the water and organic molecules can orient to minimize conformational stress around a nucleotide chain (Hammouda and Worcester 2006). A study using molecular dynamics simulations showed that a small number of highly stable water molecules and neutralization of phosphate charges are crucial requirements for the transfer of a 7-base-pair DNA duplex from water to an apolar medium such as carbon tetrachloride (Arcella et al 2014). Solvation of nucleotides in organic solutions in the presence of a small amount of water is a complex phenomenon that depends on the nature of the environment to which the nucleic acids are initially exposed (Ababneh et al 2003).…”
Section: Organic Solutions With a Small Amount Of Watermentioning
confidence: 99%
“…As computer power increases and the reliability of force fields improve, more reliable information is derived from atomistic MD simulations ( 11 ). Such simulations have revealed the extent, and the complexity, of DNA movements and their tight coupling to the nature and dynamics of the environment ( 8 , 12 14 ). Unfortunately, MD simulations are extremely dependent on the quality of the force field ( 11 , 15 17 ) and, as simulations become longer, errors induced by force fields accumulate, generating erroneous patterns of flexibility ( 18 20 ).…”
Section: Introductionmentioning
confidence: 99%
“…The incorporation of “i‐motif” sections into the DNA linker strands allows for the PAE lattices to be adjusted as a function of solution pH, as i‐motifs exhibit condensed structures at low pH and extended conformations at high pH . Unfortunately, these adjustments are often small in magnitude given that the stability of a DNA double helix is restricted to a small set of solution conditions and fairly radical changes in solvent environment tend to destabilize dsDNA …”
Section: Versatility In the Pae Constructmentioning
confidence: 99%
“…In addition to limitations in accessible core compositions, one of the major inherent limitations in the utility of PAE‐based materials synthesis is that DNA duplexes exhibit limited stability in different environments, and thus, PAE lattices are not readily usable for many different devices or applications. Some techniques have been developed to increase the stability of the PAE system after assembly, such as incorporation of intercalating elements to increase the DNA binding strength or selective nucleation of materials such as silica or silver in the vicinity of the PAE crystals, embedding them into stable states that can be removed from solution.…”
Section: Future Areas Of Investigation For Pae Crystallizationmentioning
confidence: 99%